Flipped Classroom Approach in Teaching Science in Senior High School - Plecis, Paul John; Cheung, Mary Mae (Journal of Interdisciplinary Perspectives, 2025)
Teaching in today’s classroom is a complex and challenging profession, in which the integration of technology is widely advocated to meet the demands of 21st-century learning. However, there is limited research on addressing complex topics such as Bioenergetics using the Flipped Classroom Approach. The study investigated (1) students’ economic status, ICT background, and accessibility of ICT devices; (2) students' performance before and after the implementation of the Flipped Classroom Approach, specifically in the different content areas in Bioenergetics; (3) the statistical significance of the performance of the students between the flipped and traditional classroom approaches; and (4) students’ and teacher’s experiences in using the approach. A pretest-posttest quasi-experimental design was employed with 85 Grade 11 students from a public national high school, comprising two experimental groups: 25 students from ABM, 38 from HUMSS, and a control group of 22 students from GAS. A teacher-made test, aligned with Department of Education standards, was used to assess the student's performance. Statistical analysis using ANOVA confirmed that there was no assignment bias among the groups before treatment. Results showed that the student’s performance was at the lower end of mastery before the implementation. After implementing the Flipped Classroom Approach, scores increased significantly, with students progressing toward mastery in all content areas. Statistical analysis confirmed that the experimental groups outperformed the control group, demonstrating the effectiveness of the approach. The qualitative data from the interviews and focus group discussions, using Braun and Clarke’s thematic analysis, revealed that students’ and teachers’ experiences aligned with the four pillars of F-L-I-P learning: flexible learning, learning culture, intentional content, and professional educator. The study recommends integrating the flipped classroom approach into subjects with the least learned competencies, expanding student access to ICT devices to support digital learning, and establishing a school-wide Learning Management System for effective implementation.